Web based city engineering services fault reporting system: a case study of Gweru city council engineering department - Mawarire, Takudzwa (Midlands State University, 2017)
Located in and forming part of their communities, councils are ideally positioned to search out the fine approaches to meeting local needs. Accountable for delivering an estimated eighty per cent (Andrew, et al., 2013) of public sector transactions of their areas, local authorities have a particular responsibility to design their services in probably the most accessible, monetary and ‘user-friendly’ manner. A critical function is to work intently with other public, private and voluntary sector partners to be certain that local services are citizen centric. City services fault reporting is directly linked to service delivery as is allows the citizenry to contact the local authority in regards to the services they are receiving. A Web Based City Engineering Services Fault Reporting System is an electronic system that automates the process of reporting service faults, information logging for task assignments and for attended faults. The system has been developed to meet the challenges posed by a manual system currently being used by the Gweru City Council. The system also serves to address the need to improve the citizen quality of life by providing e-solutions for interactions or communication with the city council. Using GI technology, the system provides easy to use data visualization and reporting tools.